The Factors That Will Attract and Retain Non-It Graduates in an IT-Company: The Case of IBM GDC Malaysia - Napoleon, Arrey-Mbayong (2013)
Purpose: This research is being carried out to examine some of the possible factors that can attract and retain non-IT graduates in an IT company. The main difference between this studies with similar studies carried out in the same field is that this work encompassed two theories put forward by other scholars in to one model. Other studies treated employer brand awareness and employer association as separate models. But in this study, both models where summarized into one model and tested to see if the results will lead to a possible attraction and Retention of non-IT graduates in and IT company. Methodology: This study did focus on Gen Y employees who have graduated or still to graduate as well as those already working. The sample size for this study was 300 who are students from randomly selected Universities in Klang Valley area of Malaysia, Selangor and Nilai. The study adopted a quantitative approach and surveys where distributed to target population. The data collected was analyzed with the use of SPSS 2.0 and Smart PLS software. Findings: The findings in this study reveal that employer brand awareness has an important and significant relationship with the employer brand association which in this study was represented as career growth opportunity, salary/benefits and rewards, and working environment. From the analysis it could be deduced that most IT companies don’t attract non-IT graduates because they don’t have a positive brand image. The findings also revealed that contrary to other findings, career growth opportunity do not have a significant impact on job attraction and retention. This discrepancy can be attributed to cultural differences and choice of target population. However, other variables such as salary/benefits and rewards, and working environment had a positive influence on job attraction and retention just as tested in other studies. Limitations: This study was narrowed down to a quantitative research thereby completely ignoring a blend of quantitative and qualitative study. As a consequence, much information was not obtain which would have help to better understand the concept of attracting and retaining non-IT when it comes to working in a company like IBM. The stakes of this study are high as it is an employer project, but due to time constrains, some undiscovered questions might not have been answered so as to give the employer what they really desire.